Typification of Hooker’s name Calamagrostis munroana var. stricta (Poaceae, Agrostidinae) - Paszko, Beata; Pendry, Colin A.; Kar, Sutrishna; Singh, Paramjit (Phytotaxa, 2015)
Hooker’s name Calamagrostis munroana var. stricta (Poaceae, Agrostidinae) is lectotypified by a specimen housed at the Royal Botanic Gardens, Kew (K). Pencil drawings on the Kew sheet and field labels on the CAL duplicate have provided clues to the identification of C. munroana var. stricta and to the collection locality.